Ayurvedic management of vocal cord growth: a non-invasive case study - Singla, Manisha; S., Shyam Prasad P. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Vocal cord growth can be differentiated into polyps, nodules, granulomas, and papillomas, which are benign in nature and can cause hoarseness and breathy voice. Laryngeal microsurgery is the most common conventional treatment. However, it is necessary to explore non-invasive treatment options. Objective was to report the outcome of Ayurvedic therapy in a 71-year-old female with a vocal cord growth who declined surgery. The patient presented with hoarseness of voice, vocal fatigue, and globus sensation for one month. Laryngoscopy revealed a right vocal cord growth. Patient was advised MLS under GA by an ENT expert. However, because of anxiety regarding invasive treatment, the patient wanted to explore Ayurvedic treatment options. She was treated with Lavangadi Vati, Gandamala khandan ras, marma gutika lepa, and lifestyle modifications. Significant symptomatic relief was observed within one week, with complete resolution confirmed by laryngoscopy at six weeks and sustained at follow-up. The GRBAS score improved from severe to normal in four weeks. This case suggests that Ayurvedic management may offer a non-invasive alternative solution for vocal cord growth, meriting further research.